Decoding the unsequenceable - Nathan Blow (BioTechniques)
In case you're not aware, the human genome is not completely sequenced. Regions of repeats and hard to decode sequence continue to elude scientists. And then there is the challenge of genetic variation. Nathan Blow looks at new technologies and methods that could help map these and other difficult-to-read stretches of DNA.